Rencana Pelaksanaan Pembelajaran (RPP) Guru Bahasa Inggris di SD Negeri Kunciran 6 - Alfira Fzriandina; Fitri Alia; Yanti Ardian Ningsih (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2020)
This study was to describe of Lesson Plan (RPP) of English Language at Elementary School at SD Negeri Kunciran 6 by using descriptive qualitative method. The result of study was indicator formula including the clear aspect and the completeness indicator and some part of lesson plan writing everything it was from the basic competence. Material concerned to learning indicator but only writing the essential material. Learning activity before describing the objective of right competence. The choice of resource and learning media were related to indicators. The scoring included the whole indicators, and scoring tools were not related to scoring criteria.